Knowledge and Attitudes around First Aid and Basic Life Support of Kindergarten and Elementary School Teachers and Parents in Taif City, Saudi Arabia - Shadi Tamur; Raghad Mousa Alasmari; Matooqa Abdulkareem Alnemari; Manar Abdullah Altowairgi; Atheer Hammad Altowairqi; Nouf Mohammed Alshamrani; Maryam Aljaid; Sultan Al-Malki; Abdullah Khayat; Ahmad Alzahrani; Anwar Shams (MDPI AG, 2023)
Background: The foremost cause of children's (1-19 year) death is inadvertent injuries. While most of these accidental harms occur at home and school, rapid and suitable parental and teacher intervention is required to increase the chances of a child's survival. Therefore, both parents and teachers of the children in kindergarten and elementary school must be knowledgeable in first aid practice and basic life support (BLS) training. Objectives: In the current study, our ambition is to evaluate the orientation level, knowledge, and attitudes around first aid and BLS training of kindergarten and elementary school teachers and parents in the city of Taif, Makkah region. Methods: A cross-sectional study in Taif, Saudi Arabia, targeted kindergarten and elementary school teachers and parents of students enrolled at these levels. There were 648 participants included in this study. The researchers assessed teachers' and parents' knowledge and attitudes around first aid and BLS using a validated, self-administered online questionnaire. Results: The study included 648 participants, including 248 (38.3%) teachers and 400 (61.7%) parents. The socio-demographic analysis showed that 412 (63.6%) are females and 233 (36.5%) are between the ages of 36 and 45 years. Approximately 142 (21.9%) participants reported previous training in the cardiopulmonary resuscitation (CPR) program, though more than half of them (53.5%) had outdated certificates (more than 2 years). The mean total knowledge for our study was 4.6 ± 1.4, with 22.4% of the participants being educated about first aid support and expressing a fair level of CPR foundations. Only a small percentage (2.3%) of the participants exposed a good and adequate theoretical level of knowledge around CPR skills and performance, while most of the contributors unveiled a poor level of knowledge (over 75%). There were no statistically significant differences between parents and teachers (p > 0.05). Finally, numerous participants (85%) appreciated training in the CPR program, and the most common motive was a "wish to avoid unnecessary death". Conclusions: We concluded that a sizable portion of the contributors expressed a lack of proficiency in the fundamental CPR training knowledge and skills, pointing to an alarming public concern. Promisingly, a sizable percentage of participants expressed motivated attitudes toward CPR training. Therefore, additional study and data are required to effectively combat injury, with an emphasis on investigating causes and risk factors, burden and socioeconomic health determinants, community awareness level and desire to contribute, and accessibility for disseminating specific intervention strategies.